BOS1 is a basic helix–loop–helix transcription factor involved in regulating panicle development in rice - Lv, Yanpeng; Zhang, Xinfeng; Hu, Yanjuan; Liu, Shuang; Yin, Yanbin; Wang, Xiaoxue (Frontiers in Plant Science, 2023)
Panicle development is crucial to increase grain yield of rice (Oryza sativa). The molecular mechanisms on the control of the panicle development in rice remain unclear. In this study, we identified a mutant with abnormal panicles, termed branch one seed 1-1 (bos1-1). The bos1-1 mutant showed pleiotropic defects in panicle development, such as abortion of lateral spikelets, decreased the number of primary panicle branches and secondary panicle branches. A combined map-based cloning and MutMap approaches were used to clone BOS1 gene. The bos1-1 mutation was located in chromosome 1. A T to A mutation in BOS1 was identified, which changed the codon from TAC to AAC, resulting in the amino acid change from tyrosine to asparagine. BOS gene encoded a grass-specific basic helix-loop-helix transcription factor, which is a novel allele of the previously cloned LAX PANICLE 1 (LAX1) gene. Spatial and temporal expression profile analysis showed that BOS1 was expressed in young panicles and was induced by phytohormones. The BOS1 protein was mainly localized in the nucleus. The expression of panicle development related genes, such as OsPIN2, OsPIN3, APO1, and FZP, was changed by bos1-1 mutation, suggesting the genes may be the targets of BOS1 to regulate panicle development. The analysis of BOS1 genomic variation, haplotype, and haplotype network showed that BOS1 gene had several genomic variations and haplotypes. These results laid foundation for us to further dissect the functions of BOS1.